2016
DOI: 10.1016/j.sleep.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and incident type 2 diabetes

Abstract: Objectives To determine whether severity of obstructive sleep apnea is associated with incident diabetes in middle-aged and older adults. Methods A prospective analysis of 1,453 non-diabetic participants of both the Atherosclerosis Risk in Communities Study and the Sleep Heart Health Study (mean age 63 years, 46% male) had in-home polysomnography (1996–1998) and were followed for incident diabetes. Using the apnea-hypopnea index derived from home polysomnography, study participants were categorized as follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
108
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 30 publications
6
108
2
1
Order By: Relevance
“…Our findings are corroborated by a recent study suggesting that CRP levels partially mediate the association between AHI and incident type 2 diabetes (Nagayoshi et al. ). Another recent paper demonstrated that inflammation was associated with objectively measured daytime sleepiness in patients with OSA, but not with subjectively measured sleepiness, suggesting a link between inflammation and underlying subclinical cardiometabolic dysfunction in OSA (Li et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are corroborated by a recent study suggesting that CRP levels partially mediate the association between AHI and incident type 2 diabetes (Nagayoshi et al. ). Another recent paper demonstrated that inflammation was associated with objectively measured daytime sleepiness in patients with OSA, but not with subjectively measured sleepiness, suggesting a link between inflammation and underlying subclinical cardiometabolic dysfunction in OSA (Li et al.…”
Section: Discussionsupporting
confidence: 91%
“…A more recent study demonstrated that CRP appears to mediate the association between AHI and incident type 2 diabetes (Nagayoshi et al. ), suggesting its potential efficacy in discriminating which patients with OSA may have a worse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…8,19,31 Consistent with the SDBB findings, obstructive sleep apnea has been linked with incident diabetes in a study including AAs. 32 In this study, the individual effect of each modifiable lifestyle risk factor on diabetes incidence was non-significant but in the expected direction, though this was attenuated after accounting for BMI. These results differ from larger analyses of NHWs in which ideal dietary intake, 33 higher physical activity, 19 sleep disordered breathing, 34,35 and smoking 36 were individually associated with a lower risk of developing diabetes.…”
Section: Discussionmentioning
confidence: 51%
“…In an independent manner regarding the volume of the adipose tissue, the severe form of OSA is associated with a higher risk in the case of unknown diabetes [28]. The presence of OSA should be screened in adults with type 2 diabetes, especially in males with obesity and history of heavy snoring and daytime sleepiness [29].…”
Section: Osa and Type 2 Diabetes Mellitusmentioning
confidence: 99%